Participatory action learning and action research : theory, practice and process - Wood, Lesley., 1957- (London : New York : : Routledge, Taylor & Francis Group, 2020)
"A concise yet comprehensive explanation of the theory, practice and process, this book provides the reader with everything they need to know about participatory action learning and action research (PALAR). Grounded in key theory, it draws on real-life examples of projects in various fields of study this and features critical reflections of the strengths and challenges. This book will be of interest to all students and researchers based in higher education institutions looking to learn how to engage in participatory research of a transformative, collaborative, and democratic nature to bring about change at personal, professional, organizational or community levels"--
Includes bibliographical references and index.
Keywords: Active learning; Action research in education